2006
DOI: 10.1007/bf02728967
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of silk-producing insects based on 16S ribosomal RNA and cytochrome oxidase subunit I genes

Abstract: We have examined the molecular-phylogenetic relationships between nonmulberry and mulberry silkworm species that belong to the families Saturniidae, Bombycidae and Lasiocampidae using 16S ribosomal RNA (16S rRNA) and cytochrome oxidase subunit I (coxI) gene sequences. Aligned nucleotide sequences of 16S rRNA and coxI from 14 silk-producing species were used for construction of phylogenetic trees by maximum likelihood and maximum parsimony methods. The tree topology on the basis of 16S rRNA supports monophyly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 29 publications
2
20
0
2
Order By: Relevance
“…A. assama, considered to be the progenitor species of silkmoths (Arunkumar et al, 2008a), has low chromosome number (n ¼ 15) (Deodikar et al, 1962) as compared to other known silkmoths, and female lacks W chromosome (ZO), which makes it interesting for sex-determination studies. A. mylitta, another economically important silk secreting saturniid moth (n ¼ 31), has ZW females and ZZ males (Arunkumar et al, 2008b;Mahendran et al, 2006). The study reported here shows that Aadsx and Amydsx do not have TRA/TRA-2 binding sites, instead, contain PSI binding sequences in all the female-specific transcripts similar to Bmdsx.…”
Section: Introductionmentioning
confidence: 52%
“…A. assama, considered to be the progenitor species of silkmoths (Arunkumar et al, 2008a), has low chromosome number (n ¼ 15) (Deodikar et al, 1962) as compared to other known silkmoths, and female lacks W chromosome (ZO), which makes it interesting for sex-determination studies. A. mylitta, another economically important silk secreting saturniid moth (n ¼ 31), has ZW females and ZZ males (Arunkumar et al, 2008b;Mahendran et al, 2006). The study reported here shows that Aadsx and Amydsx do not have TRA/TRA-2 binding sites, instead, contain PSI binding sequences in all the female-specific transcripts similar to Bmdsx.…”
Section: Introductionmentioning
confidence: 52%
“…Idiograms of NOR-bearing chromosomes show number and location (terminal or interstitial without closer specification) of rDNA clusters (red) in haploid complement. Phylogenetic relationships are based on Kristensen (1999), Wahlberg et al (2005), Mahendran et al (2006), Mitchell et al (2006), and Regier et al (2008). Colours of phylogenetic branches indicate the following superfamilies: grey, Gelechioidea; orange, Tortricoidea; violet, Pyraloidea; blue, Bombycoidea; yellow, Papilionoidea; green, Noctuoidea.…”
Section: Mechanisms Of Rdna Changes In Lepidopteramentioning
confidence: 99%
“…Phenol/chloroform method was used for the extraction of genomic DNA (Mahendran et al, 2006) and total RNA was extracted using TRIzol TM Reagent (Invitrogen) according to the instructions. The extracted RNA or genomic DNA was checked by electrophoresis and ultraviolet spectrum.…”
Section: Extraction Of Genomic Dna and Total Rnamentioning
confidence: 99%